Navigating and negotiating: Career changers in teacher education programmes. Issue 5 (19th October 2020) - Varadharajan, Meera; Buchanan, John; Schuck, Sandy
ABSTRACT: Career changers form a substantial proportion of teacher education (TE) students. They bring a broader set of life and work experiences than do their younger, school-leaving counterparts. This paper investigates the needs and concerns of career change student teachers (CCSTs) in Australia. The study on which this article reports analysed survey data from 508 CCSTs enrolled in 29 of Australia's 34 universities. The article explores what this group brings to their TE courses, and how their needs and contributions may differ from those of younger students. The data confirmed career changers' reasons for choosing teaching are primarily driven by intrinsic and altruistic motivations. Concerns regarding flexibility in course offerings was expressed. We advise that attracting and retaining career change teachers is likely to become increasingly important in the context of rising school student numbers, teacher attrition, and the impending departure from the profession of many 'baby boomers'.